Bidirectional relationship between pain and sleep disturbance in middle-aged and older adults: evidence from the China health and retirement longitudinal study - Yi, Duan; Yang, Mingyuan; Luo, Qipeng; Li, Hong; Kong, Liang; Cheng, Qinghao (Frontiers in Psychiatry, 2024)
BackgroundPain is one of the most prevalent symptoms that disrupt daily functioning and has been increasing in prevalence. Sleep disturbances frequently occur in individuals with pain, making it difficult to initiate and maintain sleep. This study aims to examine the bidirectional correlation between pain and sleep quality/duration among middle-aged and older Chinese adultsParticipants and settingThis study analyzed data from individuals aged 45 years and above who participated in both the 2018 and 2020 baseline surveys of China Health and Retirement Longitudinal Study (CHARLS).MethodsThe bidirectional association between pain and sleep disturbance was assessed using multivariate logistic regression models, adjusting for various covariates.ResultsAmong individuals without pain, those with unsatisfactory sleep quality were more likely to experience future pain, with an adjusted odds ratio (OR) of 1.74 (95% CI: 1.57 - 1.92). Conversely, among individuals with satisfactory sleep quality, those with pain were more likely to develop unsatisfactory sleep quality in the future, with an adjusted OR of 1.87 (95% CI: 1.69 - 2.07). Additionally, shorter sleep duration (<6 hours) was significantly associated with pain status (OR=1.39; 95% CI: 1.28 - 1.50). The incidence of developing short sleep duration in individuals with pain was also higher (OR=1.49; 95% CI: 1.38 - 1.61).ConclusionsThis research revealed a bidirectional relationship between pain and sleep disturbance in middle-aged and older Chinese adults, where each condition exacerbated the other. Recognizing and addressing this interconnected relationship was essential for effective management of both pain and sleep quality in this population.